The Microbiome, Parturition, and Timing of Birth: More questions than answers - Prince, Amanda L. (2014)
The causes of preterm birth are multifactorial, but its association with infection has been well-established. The predominant paradigm describes an ascending infection from the lower genital tract through the cervix and into the presumably sterile fetal membranes and placenta. Thus, an evaluation of the role of the vaginal microbiome in preterm birth is implicated. However, emerging fields of data described in this review suggest that the placenta might not be sterile, even in the absence of clinical infection. We thus propose an additional mechanism for placental colonization and infection: hematogenous spread. When considered in the context of decades of evidence demonstrating a strong risk of recurrence for preterm birth, studies on parturition are ideal for applying the rapidly expanding field of metagenomics and analytic pipelines. The translational implications toward identification of innovative treatments for the prevention of preterm birth are further discussed. In sum, exciting advances in understanding the role of both host and microbiota in parturition and preterm birth are on the horizon.